PENGARUH PERPUTARAN PIUTANG DAN SOLVABILITAS TERHADAP KONDISI FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR SEKTOR GARMEN DAN TEKSTIL DI BURSA EFEK INDONESIA - Siska Wulandari (Jurnal Pengembangan Wiraswasta, 2018)
Manufacture Sub Sector Garment And Textile have financial distress condition. Increas of sales is one of choice for company can be competitive in free market. But increase of sales will be followed by the many possibilities of uncollected receivable or the low receivable turnover which can effect forced the company to further provide working capital. One way is to get working capital from a third part or what we call debt.This research aims to determine the effect of receivable turnover and the solvency ratio toward the financial distressThe problems of the research were: 1) is the receivable turnover effect toward financial distress condition on Garmen and textile company Listed on IDX on 2011-2015? 2) is the leverage ratio effect toward financial distress condition on Garmen and textile company Listed on IDX on 2011-2015 ? 3) Are the receivable turnover and solvency ratio effect toward financial distress condition on Garmen and textile company Listed on IDX on 2011-2015?The sample of this research is 11 Manufacture company of sub sector Garmen And Textile were taken by using purposive sampling techniques. This research data used secondary data that getting from literature review. Data were tested using multiple linear regression analysis to determine the effect between one variable with another variables, and the data was then processed using SPSS 22.0 for windows.Result of the research showed that partially, receivables turnover hadn’t a significant effect toward the financial distress. Partially, solvency ratio (Debt to Asset) had a significant influence toward financial distress Simultaneously, receivable turnover and solvency ratio had a significant effect toward financial distress. Kata kunci:Waste Bank, Waste Bank Management, Waste Bank Basic Concepts, Economic Improvement of the Family